EFFICIENCY OF INCLUSION METFORMIN HYDROCHLORIDE TO COMBINED THERAPY OF DISEASE PSORIATIC AND METABOLIC SYNDROME - Ємченко, Я.О.; Іщейкін, К.Є. (World of Medicine and Biology, 2015)
The modern doctrine of psoriasis weighty pathogenetic role of chronic inflammation that leads to metabolic and vascular disorders. According to clinical studies, psoriasis itself as a whole may be a risk factor for atherosclerosis, which is consistent with the known concepts of chronic systemic inflammation involved in the development of diseases. Clinical and experimental studies have shown that a key role in the development of atherosclerosis and psoriasis mostly play the same cytokines (IL-1, -6, TNF α, etc.). A systemic inflammatory response, which is a common pathogenetic link at such pathological conditions alters psoriasis, which leads to severe disease which responds poorly to standard treatment significantly reduces the quality of life of patients and often leads to disability. Despite the progress made in the study of the pathogenesis of psoriatic disease and metabolic syndrome, the problem of the relationship and treatment of these diseases and the prospects for their correction, today finally clarified. The purpose of our study was to increase the efficiency of the treatment of psoriatic disease with concomitant metabolic syndrome by early correction of metabolic disorders and systemic inflammation processes. We have studied the dynamics of clinical manifestations of psoriatic disease, systemic inflammation condition and carbohydrate metabolism in patients psoriatic disease and metabolic syndrome on the background inclusion in complex therapy of metformin hydrochloride traditional. In the analysis of the results of this study found that adding metformin to standard therapy in patients with psoriatic disease with metabolic syndrome improves treatment efficacy, defined by the key indicators of the clinical status of patients, systemic inflammation and insulin resistance.
Keywords: psoriasis; metabolic syndrome; indicators of systemic inflammation; treatment